A proposed mechanism of action for the Twelve steps of Alcoholics Anonymous - Giuffra, Luis A. (2015)
Among peer-support groups for alcoholics, Alcoholics anonymous (AA) is by far the most widespread and successful with tens of thousands of groups all around the world. However, the mechanism of action of AA’s success is not immediately clear. Advances in understanding the neuroscience of addiction have allowed the identification of two brain areas that, among others, explain the irrational and self-destructive behavior of alcoholics. First, alcohol hijacks the reward systems of the midbrain in charge of detecting and experiencing pleasure (through the release of dopamine in the nucleus accumbens and the ventral tegmental area) with a pleasurable stimulation that far exceeds the normal pleasures of life (such as eating and sexual reproduction). These pleasurable experiences are essential for the survival and evolution of the species. Nature has cleverly linked pleasure with survival, and it is exactly this link that is usurped and hijacked by intoxicants like alcohol. Therefore, the reward system senses the effect of alcohol as essential for the survival of the alcoholic. In addition, the prefrontal cortex (perhaps the only area of the brain that could allow us to understand and prevent the dangers of the excessive and compulsive alcohol use) is also affected by this intoxicant. It becomes hypoactive and unable to counteract the urges and demands of the reward system to constantly repeat the “feel good” (associated over millions of years with survival of the individual and species) that comes from using alcohol. The Twelve Steps of AA help alcoholics reverse these effects. First, through steps 1 to 3, it encourages the use of a Surrogate Decision-Maker (often, it is the AA group itself that acts as such). Second, steps 4- 12 foster the practice of Compensatory Behaviors (a life of honesty and service) devoted to counteract the maladaptive behaviors that facilitate the alcoholic’s behavior of repeating what feels good (i.e. getting intoxicated). Lying, stealing, dishonesty and manipulation are not intrinsic personality defects of the alcoholic: they are the symptoms of a usurped reward system and hijacked prefrontal lobes.